Product quality and price in deciding to repurchase rice Batang Girl - Hartelina Hartelina; Syifa Pramudita Faddila; Yanu Prasetyo; Thuwi Wulakrisna (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Karawang Rice Agent is one of the rice producing villages in Sentra Bizhub, BLOK B2 Teluk Jambe Timur, Karawang. There are various types of rice produced, such as hybrid rice, virgin rice, jasmine rice and so on. Apart from that, the rice produced by Jaya Makmur Village is not consumed by the community itself, some is also sold in various sub-districts and districts. The aim of this studyto determine the relationship between product quality and price on interest in buying rice at the Batang Girl rice agent in Karawang, with customer satisfaction as the intervention variable. A nonprobability sampling technique was used in this research, where 60 Karawang rice agent consumers were selected as samples. Testing was carried out using validity, reliability, mediation and hypothesis testing tools with the help of the WarPPL version 3.0 program. Hypothesis test results show that product quality (X1) has a significant positive effect on customer satisfaction (Z), with a path coefficient of 0.93. Apart from that, the R-Square of 0.87 shows that product quality has a large influence of 87% on customer satisfaction. Furthermore, the results of the hypothesis test show that price (X2) also has a significant positive effect on customer satisfaction (Z), with a path coefficient of 0.83. An R-Square of 0.78 indicates that price has a large influence of 78% on customer satisfaction. Furthermore, the results of hypothesis testing show that customer satisfaction (Z) has a significant positive effect on repurchase intention, with a path coefficient of 0.98. An R-Square of 0.97 indicates that customer satisfaction has a very large influence of 97% on repurchase intention. Based on these findings, it can be concluded that product quality and price have a significant effect on customer satisfaction which in turn has an impact on repurchase intention. The implications of these findings reflect the importance of maintaining product quality and setting appropriate prices in an effort to increase customer satisfaction, which in turn can increase repeat purchase intention. By further understanding these dynamics, Batang Girl rice agents in Karawang can optimize their marketing strategies to achieve long-term success in a competitive market.